Organ-specific proteomic responses to tetrodotoxin administration in the liver and skin of Takifugu rubripes - Natsuki Ono; Ryohei Tatsuno; Emiko Koba; Takeshi Bamba; Yuki Takai; Abrianna Elke Chairil; Zhaoya Li; Shoma Inoue; Hayato Kimura; Kazuma Kitamura; Masato Honda; Kenichi Yamaguchi; et al. (Toxicon, 2026)

Intraoperative Language mapping in a Japanese-English-French trilingual patient with a left Temporal lobe glioma: a case report - Kosei Yamamoto; Ryota Tamura; Sara Ganaha; Kosuke Karatsu; Tomoko Ishizawa; Kazuhiro Kojima; Makiko Ando; Kenzo Kosugi; Yohei Kitamura; Ryo Ueda; Aiko Ishikawa; Tomoyuki Imanishi; et al. (Brain Structure and Function, 2025)

Lowering of the kinetic barrier of clay-mineral reactions along a seismogenic fault: Example from the Nankai subduction zone, Japan - Hirokazu Masumoto; Jun Kameda; Yohei Hamada; Kohtaro Ujiie; Yujin Kitamura (Tectonophysics, 2023)

Modulation of corticospinal excitability related to the forearm muscle during robot-assisted stepping in humans - Taku Kitamura; Yohei Masugi; Shin-ichiroh Yamamoto; Toru Ogata; Noritaka Kawashima; Kimitaka Nakazawa (Experimental Brain Research, 2023)
In recent years, the neural control mechanisms of the arms and legs during human bipedal walking have been clarified. Rhythmic leg stepping leads to suppression of monosynaptic reflex excitability in forearm muscles. However, it is unknown whether and how corticospinal excitability of the forearm muscle is modulated during leg stepping. The purpose of the present study was to investigate the excitability of the corticospinal tract in the forearm muscle during passive and voluntary stepping. To compare the neural effects on corticospinal excitability to those on monosynaptic reflex excitability, the present study also assessed the excitability of the H-reflex in the forearm muscle during both types of stepping. A robotic gait orthosis was used to produce leg stepping movements similar to those of normal walking. Motor evoked potentials (MEPs) and H-reflexes were evoked in the flexor carpi radialis (FCR) muscle during passive and voluntary stepping. The results showed that FCR MEP amplitudes were significantly enhanced during the mid-stance and terminal-swing phases of voluntary stepping, while there was no significant difference between the phases during passive stepping. Conversely, the FCR H-reflex was suppressed during both voluntary and passive stepping, compared to the standing condition. The present results demonstrated that voluntary commands to leg muscles, combined with somatosensory inputs, may facilitate corticospinal excitability in the forearm muscle, and that somatosensory inputs during walking play a major role in monosynaptic reflex suppression in forearm muscle.

Evaluation of white Kwao Krua (Pueraria candollei Grah. ex Benth.) products sold in Thailand by molecular, chemical, and microscopic analyses - Aekkhaluck Intharuksa; Masashi Kitamura; Nichakan Peerakam; Wannaree Charoensup; Hirokazu Ando; Yohei Sasaki; Panee Sirisa-ard (Journal of Natural Medicines, 2020)

Morphological and genetic differences between Coptis japonica var. anemonifolia H. Ohba and Coptis japonica var. major Satake in Hokuriku area - Masashi Kitamura; Hirokazu Ando; Yohei Sasaki (Journal of Natural Medicines, 2018)

Three‐dimensional texture of natural pseudotachylyte: Pseudotachylyte formation mechanism in hydrous accretionary complex - Yohei Hamada; Gaku Kimura; Jun Kameda; Asuka Yamaguchi; Mari Hamahashi; Rina Fukuchi; Yujin Kitamura; Shin'ya Okamoto (Island Arc, 2018)
Melt‐origin pseudotachylyte is the most reliable seismogenic fault rock. It is commonly believed that pseudotachylyte generation is rare in the plate subduction zone where interstitial fluids are abundant and can trigger dynamic fault‐weakening mechanisms such as thermal pressurization. Some recent studies, however, have discovered pseudotachylyte‐bearing faults in exhumed ancient accretionary complexes, indicating that frictional melting also occurrs during earthquakes in subduction zones. To clarify the pseudotachylyte generation mechanism and the variation of slip behavior in the plate subduction zone, a pseudotachylyte found in the exhumed fossil accretionary complex (the Shimanto Belt, Nobeoka, Japan) was re‐focused and microscopic and three‐dimensional observations of the pseudotachylyte‐bearing fault were performed based on optical, electron, and X‐ray microscope images. Based on the patterns contained in the fragment, the pseudotachylyte is divided into four domains, although no clear domain boundaries or layering structures are not found. Three‐dimensional observation also suggests that the pseudotachylyte were fragmented or isolated by cataclasite or carbonate breccia. The pseudotachylyte was rather injected into the surrounding carbonate breccia, which is composed of angular fragments of the host rock and a matrix of tiny crystalline carbonate. The pseudotachylyte volume was extracted from the X‐ray microscope image and the heat abundance consumed by the pseudotachylyte generation was estimated at 2.18 MJ/m 2 , which can be supplied during a slip of approximately 0.5 m. These observations and calculations, together with the results of the previous investigations, suggest hydrofracturing and rapid carbonate precipitation that preceded or accompanied the frictional melting. Dynamic hydrofracturing during a slip can be caused by rapid fluid pressurization, and can induce abrupt decrease in fluid pressure while drastically enhancing the shear strength of the shear zone. Consequently, frictional heating would be reactivated and generate the pseudotachylyte. These deformation processes can explain pseudotachylyte generation in hydrous faults with the impermeable wall rock.

Acoustic properties of deformed rocks in the N obeoka thrust, in the S himanto B elt, K yushu, S outhwest J apan - Yoshitaka Hashimoto; Shogo Abe; Hiroki Tano; Mari Hamahashi; Saneatsu Saito; Gaku Kimura; Asuka Yamaguchi; Rina Fukuchi; Jun Kameda; Yohei Hamada; Yujin Kitamura; Koichiro Fujimoto; et al. (Island Arc, 2017)
Laboratory measurements for compressional and shear wave velocities ( V p and V s, respectively) and porosity were conducted with core samples from the N obeoka T hrust D rilling P roject ( NOBELL ) under controlled effective pressure (5–65 MPa at 5 MPa intervals) and wet conditions. Samples were classified according to deformation texture as phyllite, foliated cataclasite, or non‐foliated cataclasite. Measured values of V p, V s, and porosity are within a range of 5.17–5.57 km/s, 2.60–2.71 km/s, and 2.75–3.10 %, respectively, for phyllite; 4.89–5.23 km/s, 2.46–2.57 km/s, and 3.58–4.53 %, respectively, for foliated cataclasite; and 4.90–5.32 km/s, 2.51–2.63 km/s, and 3.79–4.60 %, respectively, for non‐foliated cataclasite, which are all consistent with the previous laboratory experiments conducted with outcrop samples under dry conditions. However, our results also indicate higher V p and V s and lower porosity than those measured by the previous studies that adopted the wire‐line logging methods. The variations in V p, V s, and porosity are controlled by deformation structure and are greater for phyllite and foliated cataclasite than for non‐foliated cataclasite.

Temporal stress variations along a seismogenic megasplay fault in the subduction zone: A n example from the N obeoka T hrust, southwestern J apan - Ryoji Kawasaki; Mari Hamahashi; Yoshitaka Hashimoto; Makoto Otsubo; Asuka Yamaguchi; Yujin Kitamura; Jun Kameda; Yohei Hamada; Rina Fukuchi; Gaku Kimura (Island Arc, 2017)
The N obeoka T hrust, an ancient megasplay fault in the S himanto B elt, southwestern J apan, contains fault rocks from the seismogenic zone, providing an accessible analog of active megasplay faults in deep subduction settings. In this study, the paleostress along the N obeoka T hrust was analyzed using multiple inversion techniques, including k ‐means clustering of fault datasets acquired from drillcores that intersected the thrust. The six resultant stress orientation clusters can be divided into two general groups: stress solutions with north–south‐trending σ 1 axes, and those with east–west‐trending σ 1 axes. These groups are characterized by the temporal changes for the orientations of the σ 1 and σ 3 principal stress axes that involve alternation between horizontal and vertical. The findings are probably due to a change in stress state before and after earthquakes that occurred on the fault; similar changes have been observed in active tectonic settings, such as the 2011 T ohoku‐ O ki earthquake ( J apan).

Rapid identification of drug-type strains in Cannabis sativa using loop-mediated isothermal amplification assay - Masashi Kitamura; Masako Aragane; Kou Nakamura; Kazuhito Watanabe; Yohei Sasaki (Journal of Natural Medicines, 2017)

Knee extensor strength is associated with Mini-Mental State Examination scores in elderly men - Hiroki Nakamoto; Yasuhide Yoshitake; Yohei Takai; Hiroaki Kanehisa; Takahiro Kitamura; Masashi Kawanishi; Shiro Mori (European Journal of Applied Physiology, 2012)